Preliminary study of flavonoids in banana's nectar - Aimi Syazana, Sedek (Universiti Malaysia Sarawak (UNIMAS), 2015)
Bananas are classified in Zingiberales order, Musaceae family, and falls into genus Musa. Banana is rich in phenolic acids and flavonoids, which exhibit a wide range of biological effects besides acting as natural anti-oxidants. This study aimed to investigate flavonoid and sugar content in the nectar of two wild species of banana; Musa acuminata and Musa campestris. Paper chromatography were used for both analyses. Several classes of flavonoid have been identified in both species, namely flavonols, flavone glycosides and flavonone. Meanwhile, sugars arabinose, ribose and apiose were the main sugars present in the nectar. Flavonoid aglycone however, failed to give consistent result after several analyses run. Further investigation are needed to confirm the aglycone result.